A review of location-based games: Do they all support exercise, social interaction and cartographical training? - Samuli Laato; Tarja Pietarinen; Sampsa Rauti; Nobufumi Inaba; Erkki Sutinen (Portugal, 2022)
Studies on location-based games ubiquitously report positive learning outcomes for the players. Particularly these games are shown to promote exercise, encourage to social interaction and increase geographical and cartographical knowledge. To find out whether these positive effects are game-specific or characteristic to all location-based games, we conduct a software search for available location-based games on iOS and Android platforms and evaluate if and how exercise, cartographical training and social interaction are supported. Based on our results we were able to identify six sub-genres of location-based games, and the positive effects associated with each genre. The most popular category in terms of number of games was scavenger hunts and the most popular category in terms of active installs on Android and iOS was location-based MMORPG’s. Presence of factors associated with immersion and mixed reality were paired with the popularity and positive outcomes of the games. Cartographi cal practise, social interaction and exercise were supported the most in the location-based MMORPG sub-genre, to which, for example, Pokémon GO belongs to
Proceedings of the 11th International Conference on Computer Supported Education - (Volume 1)